High-Capacity Reversible Data Hiding in Encrypted Images by Bit Plane Partition and MSB Prediction - Hao-Tian Wu; Zhiyuan Yang; Yiu-Ming Cheung; Lingling Xu; Shaohua Tang (IEEE Access, 2019)
This paper proposes a high-capacity scheme for reversible data hiding (RDH) in encrypted images. The proposed scheme is based on a new preprocessing method by bit plane partition. Specifically, the values in the less significant bit planes are reversibly hidden into the other bit planes. Consequently, the room in the less significant bit planes can be vacated to generate a preprocessed image, from which the original image can be recovered by extracting the hidden bit values and writing them back. After encrypting the preprocessed image with a stream cipher, the vacated room can be used to accommodate extra data, which can be retrieved without image decryption. In addition, the embedding capacity can be further increased by adopting an efficient most significant bit (MSB) prediction method before image encryption. Compared with the state-of-the-art RDH schemes for encrypted images, the experimental results show that higher embedding capacity can be achieved with our proposed one. The numerical results are provided to show the performances of the proposed scheme in different cases of bit-plane partition and MSB prediction.